Concepts by nursing scholars about depression and care for depressed patients - Medeiros de Moura, Marina Gabriela; Pereira Feitosa, Izayana; Agra, Glenda; Bernardo de Lima, Gigliola Marcos; Pedrosa de Lima, Itacira; Alves Sucupira, Polianna (O Mundo da Saúde, 2015)
Depressive disorder is the most common mental disorder and it is considered a serious public health problem. It is be- lieved that knowledge about depression has a fundamental importance for professional nurses, given their role implies a direct contact with patienst, acting as an active participant in the identification and treatment of various mental disorders. This study aimed to identify the concepts about depression of academics of an undergraduate nursing course at Federal University of Campina Grande, Campus Cuité, Paraíba. This is a descriptive study under the perspective of a qualitative ap- proach, carried out through the participation of nursing students who responded to a semi-structured questionnaire versed on the subject of depression. The results were analyzed by means of the technique of content analysis proposed by Bardin. The results showed that most students judge their knowledge as good or regular and they gave justified it in particular by means of the need for improvement and lack of practical field work. It is also noted that participants, despite the responses shown previously, have also shown in their answers an important, holistic and humane conception of nursing care. As for didactics, the students presented the traditional method as preponderant in teaching about the disorder and proposed that improvements in education could be achieved with the use of active methodologies and articulation of theory with practice.